2022
DOI: 10.1111/aor.14161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy between hemodialysis using super high‐flux dialyzer with hemoperfusion and high‐volume postdilution online hemodiafiltration in removing protein bound and middle molecule uremic toxins: A cross‐over randomized controlled trial

Abstract: Background: Hemodialysis (HD) using super high-flux dialyzer (HD + SHF) comparably removed uremic toxins to high-volume postdilution online hemodiafiltration (olHDF). Integration of hemoperfusion (HP) to HD + SHF (HD + SHF + HP) might provide superior uremic toxin removing capability to high-volume postdilution olHDF. Method:The present study was conducted in thrice-a-week HD patients to compare the efficacy in removing indoxyl sulfate (IS), beta-2 microglobulin (β 2 M), and urea between high-volume postdiluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, clinical treatment strategies are optimized by combining HP with HD [23]. Tiranathanagul K, et al had Compared the effects of high-flux dialyzer with 2 hours of hemofusion and high volume post-dilution online hemodiafiltration on uremic toxin clearance, it was found that HD+HP was not superior to HDF [24].Here, the study found the high flux dialysis combined with hemoperfusion (HP cartridge containing 160 ml resin; OCI Medical Devices Co., Ltd, Chengdu, China) that the clearance of Indoxyl sulfate was higher than high flux dialysis and hemodiafiltration (41.53%, 17.19%, 22.79%), and 4 hours was better than 2 hours (45.53%, 26.94%). However, the clearance of small molecular and water soluble uremic toxins is not superior to high flux dialysis and hemodiafiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical treatment strategies are optimized by combining HP with HD [23]. Tiranathanagul K, et al had Compared the effects of high-flux dialyzer with 2 hours of hemofusion and high volume post-dilution online hemodiafiltration on uremic toxin clearance, it was found that HD+HP was not superior to HDF [24].Here, the study found the high flux dialysis combined with hemoperfusion (HP cartridge containing 160 ml resin; OCI Medical Devices Co., Ltd, Chengdu, China) that the clearance of Indoxyl sulfate was higher than high flux dialysis and hemodiafiltration (41.53%, 17.19%, 22.79%), and 4 hours was better than 2 hours (45.53%, 26.94%). However, the clearance of small molecular and water soluble uremic toxins is not superior to high flux dialysis and hemodiafiltration.…”
Section: Discussionmentioning
confidence: 99%
“…From our point of view, possible reasons included the following: (1) HFHD+HDF better cleared some unknown medium and large molecule uraemic solutes/toxins, which are associated with anemia and may inhibit erythropoiesis or cause erythropoietin resistance 28 . The toxins that may be eliminated by HFHD + HDF include β2M and the urea reduction ratio 29 (2) Since patients treated with HFHD + HDF have a higher quality of life, they may have an improvement in anorexia and therefore may have a better nutritional intake, resulting in improved erythrocyte production. This is a presumed indirect effect.…”
Section: Discussionmentioning
confidence: 99%
“…The HF membrane is the standard of care and would reflect the routine clinical practice in middle-and high-income countries [31]. Tiranathanagul et al [68] executed a study comparing HF hemodiafiltration versus MCO HD plus hemoadsorption with the HA130 cartridge (Jafron Biomedical, Zhuhai City, China), containing microspheres made of styrene-divinylbenzene. The study had a crossover design and randomized 10 patients previously on HF HD to carry out 6 sessions of either MCO HD or HF hemodiafiltration (phase 1), followed by a 2-week wash-out period in which patients returned to HF HD (phase 2).…”
Section: Adsorptionmentioning
confidence: 99%